2009
DOI: 10.1073/pnas.0906541106
|View full text |Cite
|
Sign up to set email alerts
|

Endosomes: A legitimate platform for the signaling train

Abstract: Although long regarded as a conduit for the degradation or recycling of cell surface receptors, the endosomal system is also an essential site of signal transduction. Activated receptors accumulate in endosomes, and certain signaling components are exclusively localized to endosomes. Receptors can continue to transmit signals from endosomes that are different from those that arise from the plasma membrane, resulting in distinct physiological responses. Endosomal signaling is widespread in metazoans and plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
339
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(358 citation statements)
references
References 99 publications
(120 reference statements)
10
339
1
2
Order By: Relevance
“…Although active signaling from within endosomes has been reported for a selected group of membrane receptors (reviewed in refs. [23][24][25], here we directly demonstrate that internalized CD3ζ is signaling competent. The important, albeit nontrivial, questions that remain to be answered are whether distinct TcR/CD3-dependent signaling pathways can be traced specifically to the plasma-membrane and intracellular pools of CD3ζ and how these pathways depend on TcR/CD3 trafficking within the cell.…”
Section: Discussionmentioning
confidence: 84%
“…Although active signaling from within endosomes has been reported for a selected group of membrane receptors (reviewed in refs. [23][24][25], here we directly demonstrate that internalized CD3ζ is signaling competent. The important, albeit nontrivial, questions that remain to be answered are whether distinct TcR/CD3-dependent signaling pathways can be traced specifically to the plasma-membrane and intracellular pools of CD3ζ and how these pathways depend on TcR/CD3 trafficking within the cell.…”
Section: Discussionmentioning
confidence: 84%
“…Unlike other G‐protein‐coupled receptors that rapidly internalize following stimulation to terminate signaling,69 CXCR4 exhibits a prolonged stimulatory capacity attributed to endosomal signaling. Recruitment of signaling complexes, which can include both inhibitors or activators of signaling, to endosomes determines the signal type 70. Given that the presence of sCD74 did not inhibit MIF‐induced internalization of either CXCR2 or CXCR4, sCD74 might diminish MIF‐mediated endosomal signaling 69.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that EGFR and other RTKs, are also capable of recruiting signaling molecules and transmitting signals from endosomes (7,9,10). Moreover, it was proposed that following EGFR activation clathrin mediated endocytosis plays an important regulatory role in control of sustained activation of the MAPK/ERK signaling pathway and in Akt stimulation (4,11).…”
mentioning
confidence: 99%
“…Moreover, it was proposed that following EGFR activation clathrin mediated endocytosis plays an important regulatory role in control of sustained activation of the MAPK/ERK signaling pathway and in Akt stimulation (4,11). The current prevailing view is that signals induced by activated EGFR and other RTKs can be transmitted from the plasma membrane as well as from endosomes and that the spatial localizations of RTKs play an important role in the control of signal specificity, duration, and robustness (4,(9)(10)(11)(12).…”
mentioning
confidence: 99%